High–Energy‐Storage Density Capacitors of Bi(Ni1/2Ti1/2)O3–PbTiO3 Thin Films with Good Temperature Stability. Issue 7 (14th June 2013) - Xie, Zhenkun; Peng, Bin; Meng, Siqin; Zhou, Yuanyuan; Yue, Zhenxing
Abstract : High–energy‐storage density capacitors with thin films of 0.5Bi(Ni1/2 Ti1/2 )O3 –0.5PbTiO3 (BNT–PT) were fabricated by chemical solution deposition technique on Pt/Ti/SiO2 /Si substrates. The dense thin films with pure‐phase perovskite structure could be obtained by annealing at 750°C. High capacitance density (~1925 nF/cm 2 at 1 kHz) and extremely high‐energy density (~45.1 J/cm 3 ) under an electric field of 2250 kV/cm were achieved at room temperature. The energy‐storage density and efficiency varied little in a wide temperature range from −190°C to 250°C. The high–energy‐storage density and good temperature stability make BNT–PT films promising candidates for high power electric applications.